(3GdGjVGMs - (3fGUQ Hf YHO GdSjO CHj GdecGQe GHf Ydj, CHh GdaJM, HQgGf GdOjf GdNhGQRej GdeWQRj , J (B610 (3g`s; (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeMehO Ydi LejY GdGdGA GdeTchQ HMSf GdHdGA hHYO aEfi de CQ ai cJH GdYQHjI hGdGOH cJGHkG CMSf JCdjakG ef GdebGeGJ s
(3BNQgG (B:s
(3Jbhd fUH Yjfi HGdVe hgh ai GdCUd GSe dcd eG jfUH aYd HeYfi eaYhd cGdCcd hGdWYe HeYfi GdeCchd hGdeWYhe hGddg JYGdi CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
Keywords: (3GdCOHs